2021
DOI: 10.1371/journal.pntd.0009483
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity and Specificity of two rapid tests for the diagnosis of infection by Trypanosoma cruzi in a Colombian population

Abstract: Objective To evaluate diagnostic precision of two rapid diagnostic tests (RDT’s) on patients with chronic Chagas disease. Methodology Prospective study with the following inclusion criteria: subjects older than 3 years, signed informed consent. Exclusion criterion: subjects could not have previously received treatment for infection with T. cruzi. The study population were participants in a screening process undertaken in rural and urban zones of the department Boyacá, Colombia. Two RDT’s were performed to al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…Although rapid tests have a high sensitivity rate of almost 100%, there have been significant variations in their performance in Mexico and the USA due to differences in circulating DTUs in each region 46 . Rapid tests have shown outstanding performance in countries like Colombia and Bolivia 47,48 . To accurately diagnose infections, it is important to develop targeted diagnostic tests for the circulating DTUs in each region.…”
Section: Discussionmentioning
confidence: 99%
“…Although rapid tests have a high sensitivity rate of almost 100%, there have been significant variations in their performance in Mexico and the USA due to differences in circulating DTUs in each region 46 . Rapid tests have shown outstanding performance in countries like Colombia and Bolivia 47,48 . To accurately diagnose infections, it is important to develop targeted diagnostic tests for the circulating DTUs in each region.…”
Section: Discussionmentioning
confidence: 99%
“…Data were entered into Origin 2020b and are presented as histograms. The kappa ( K ) coefficient was employed to measure agreement between two methods, which allowed us to measure agreement beyond what was expected by chance alone [ 32 , 33 ]. The generic formula for K is where P o and P e are the observed and expected proportions of agreement [ 34 ].…”
Section: Methodsmentioning
confidence: 99%
“…However, to follow the recommended diagnosis algorithm, positive cases still must be confirmed by a conventional immunoassay [31]. In this sense, studies have shown promising results regarding the synchronous combination of two rapid tests with different antigen composition as an alternative strategy for definitive diagnosis in low-resources settings in Bolivia, Argentina, and Colombia [28,31,[34][35][36][37]. The association of two rapid tests displayed ≥93.3% of diagnostic efficiency when using results obtained by at least two conventional immunoassays as reference [28,31,35,36].…”
Section: Applicability Of Rapids Tests and Its Perspectives In CD Con...mentioning
confidence: 99%
“…In this sense, studies have shown promising results regarding the synchronous combination of two rapid tests with different antigen composition as an alternative strategy for definitive diagnosis in low-resources settings in Bolivia, Argentina, and Colombia [28,31,[34][35][36][37]. The association of two rapid tests displayed ≥93.3% of diagnostic efficiency when using results obtained by at least two conventional immunoassays as reference [28,31,35,36]. This alternative protocol has a great advantage in speeding up the process of patient continued medical assistance, especially regarding the offer of trypanocidal drugs and, eventually, other necessary treatments.…”
Section: Applicability Of Rapids Tests and Its Perspectives In CD Con...mentioning
confidence: 99%
See 1 more Smart Citation